Interference reduction using MMSE-DFE equalizer with one-third ICI-SC STFBC for MIMO-OFDMA system - Adiba, Hanis; Idris, Azlina; Dimyati, Kaharudin; Andriana, Ratna; Kassim, Murizah; Rahman, Ruhani Abdul (Universiti Teknikal Malaysia Melaka, 2018)
Orthogonal frequency division multiple access (OFDMA) allows simultaneous low data rate transmission for several users. However, as one symbol interferes with subsequent symbol, it will produce a phenomenon called intersymbol interference (ISI) which has similar effect as noise and thus making the communication less reliable. Besides that, Doppler spread due to channel time-variation destroys the orthogonality in OFDMA system and degrade the system performance with intercarrier interference (ICI). In order to solve this issue, minimum mean square error-decision feedback equalizer (MMSE-DFE) with one-third (ICI-SC) subcarrier mapping method using space-time-frequency block codes (STFBC) is proposed. The objective is to minimize both ISI and ICI effects by evaluating pairwise error probability (PEP) and bit error rate (BER) performances. From the simulation results, MMSE-DFE with one-third ICI-SC technique shows the best result for MIMO-OFDMA system with 25% improvement of PEP and 4.8% improvement of BER.